Seroprevalence and Risk of Toxoplasma gondii Reactivation in Pediatric Patients with Hematological Malignancies Undergoing Chemotherapy: A Case-Control Study - Abdolkarimi, Babak; Mahmmodvand, Hosein; Beyranvand, Neda; Naderi, Narges; Amidi, Bardia (Archive of Oncology, 2025)
Background: Toxoplasmosis, caused by Toxoplasma gondii, affects around 40% of the Iranian population and can be severe in vulnerable patients, such as those receiving chemotherapy.  In this study, the titers of IgG and IgM antibodies in 92 children treated for chemotherapy have been compared with 92 matched controls. We also looked into demographic and lifestyle factors in association with the antibody levels as a contribution to the development of improved preventive and management techniques.Methods: In this case-control study conducted at Shahid Madani Hospital, Khorramabad, Iran, blood samples of both groups were tested for IgG and IgM anti-Toxoplasma gondii antibodies by ELISA. Participants were selected randomly, and demographic, clinical, and lifestyle data were obtained from structured interviews and from the hospital records. Statistical analyses were performed using SPSS software, considering p-values less than 0.05 as significant. Approval for ethics was obtained, and informed consent was provided by the guardians.Results: The results revealed that the prevalence of IgG antibodies was significantly higher in chemotherapy patients (35.9%) compared to the controls (14.1%), indicating a strong association between immunosuppression and elevated IgG levels (p = 0.001, OR = 2.026). No significant difference in IgM antibodies was found, suggesting that chemotherapy increases the risk of reactivation rather than new infections. Subgroup analysis showed that IgG positivity was more common in younger immunocompromised patients (under 10 years old). However, factors such as gender, residence, and dietary habits did not significantly affect IgG or IgM positivity. In the control group, urban residents had a higher IgG positivity rate than rural ones.Conclusion: In conclusion, pediatric patients who have undergone chemotherapy are more prone to chronic infection with Toxoplasma gondii. Serological tests and prevention measures must be carried out regularly to reduce the risk of reactivation in such patients.
Keywords: Toxoplasma; Seroepidemiologic Studies; Hematologic Neoplasms